A Study to Evaluate Internet Addiction Disorder Among Students of a Medical College and Associated Hospital of Central India - Malviya, Amit; Dixit, Sanjay; Shukla, Harish; Mishra, Ankita; Jain, Abhineet; Tripathi, Amrita (National Journal of Community Medicine, 2014)
Background: Internet Addiction is an addiction like any other: it is defined as a compulsive loss of impulse control resulting in damage to the user and his or her relationships, schoolwork, or employment. Online gaming, compulsive use of social networking, and marathon Internet surfing sessions are all included in this powerful addition. Objective: To study Internet dependence among undergraduate students of MGM Medical College Indore and to determine prevalence of Internet addiction disorder among these students. Materials and Methods: A cross sectional study was carried out from Sept.2011 to January 2012 among 242 undergraduates of MGM Medical College of Indore city selected by simple random sampling. The data was collected by inter personal interviews using a standardized ‘Internet Addiction Test’ questionnaire developed by Dr. Kimberly S. Young in 1998. Results: Among 242 study subjects, 164 (67.8%) were males and 78 (32.2%) were females. Overall analysis to find out proportion of study subjects falling in the category of internet addicts on the basis of scoring system adapted for the study reveals that 23 (9.5%) subjects have been found to be internet addicts i.e. have scores 80-100. Among 23 (9.5%) internet addicts found in the study, 15 (6.1%) were males and 8 (3.3%) were females. (n=242). Conclusion: The data is indicative of Internet addiction to be an emerging problem of the modern era